La redistribución del territorio político electoral en Tlaxcala y su influencia en el sistema de partidos: 1992-2004 - Alacio García, Rosa Ynés (Universidad Autónoma Metropolitana, 2006)
Political territorial changes in Tlaxcala influenced on the party system from 1992 to 2004 when differents parties won the local government power. How does the party system change when introducing reforms that change the political and electoral territory? There is an interdependence between the electoral system and the party system. In Tlaxcala, territorial changes influenced the party system and now there are competitive processes and volatile elections. This study shows regional differences in Tlaxcala and the influence of the political territorial changes on the party system. Legal changes in the political and electoral territory were developed first in the parliament seats and later in the municipalities. Those changes appeared in the State Constitution and in the Local Electoral Law. Chapter 1 discusses those Constitutional Reforms and the territorial changes. When the parliament seats increased the number of representative parties increased in the Congress and the rivalry, too. The districts changed but how did it happen? Chapter 2 presents the changes in the parliament seats, the new political scenery, and the consequences for the local party system. Chapter 3 shows the Tlaxcala’s regions in differents ways, one of this through a social-demographic and economic analysis. Which are the characteristics of the municipalities in Tlaxcala and how can explain the votes in the regions. Why are the regions important in the electoral and political territory design? The competitiveness and volatility in the party system of the municipalities process appeared when the local goverment increased from 44 to 60 in Tlaxcala. It happened in 1995 when 16 communities were separated from their municipalities. They were declared new municipalities. After those changes, the parties electoral participation was high and at least five parties won the local power, it was very important because a hegemonic party existed in this State. Chapter 4 discusses those changes since a regional analysis.